Holistic Preschool Guidance Model in Muhammadiyah Orphanage: Model Bimbingan Holistik untuk Taman Kanak-Kanak di Panti Asuhan Muhammadiyah - Isatin Rodiyah; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Orphanages function not only as social care institutions but also as educational environments for early childhood development. Specific Background: Children in orphanages often experience family dysfunction, requiring structured guidance that integrates character education, religious values, and developmental support. Knowledge Gap: Limited studies describe comprehensive preschool guidance patterns implemented within faith-based orphanage settings. Aims: This study aims to explore the patterns of guidance for preschool-aged children at Muhammadiyah Pagesangan Orphanage. Results: Using a qualitative descriptive approach involving four caregivers and six foster children, data were collected through observation, interviews, and documentation. Findings show that the orphanage applies a holistic model encompassing physical development, religious and moral cultivation, intellectual growth, social interaction, and vocational preparation. Daily religious practices, character habituation, group activities, and environmental responsibility programs form core components of guidance. Supporting factors include organizational backing and trained caregivers, while financial limitations and diverse child backgrounds present challenges. Novelty: The study provides an integrated description of preschool guidance within a Muhammadiyah orphanage context. Implications: Balanced and continuous implementation of physical, spiritual, intellectual, and vocational guidance supports the formation of independent and morally grounded children. Keywords: Preschool Guidance, Orphanage Education, Character Development, Caregiver Role, Early Childhood Education Key Findings Highlights: Integrated developmental approach covers moral, cognitive, social, and physical domains. Daily structured religious routines shape ethical behavior formation. Institutional support and caregiver capacity coexist with resource constraints.